Interdependance, linkage et système international : de l'analyse conceptuelle aux problèmes de politique étrangère - Seminatore, Irnerio (Études internationales, 1987)
The emergence and evolution of the literature dealing with interdependence in the international System is looked into. An attempt is made to show its significance and main points as well as its implications. The debates on interdependence within the North-American political context are regarded as solutions to the preceding issues on dependence. Interesting passages are dedicated to the impact of the interdependence theory on the interpretation of the international system, as illustrated by two schools of thought in foreign policy (Kissinger-Brzezinski). Linkage of the tactical and strategic aspects to the economic and political interrelation of international relations, as put forward by policy makers, has brought to the fore the difficulties and limits of negotiation in the face of competition and in the aftermath of confrontation. This paper offers subtle, yet positive, conclusions on the use of the interdependance theory in international policy.